EARNINGS QUALITY AS A MODERATOR OF DIVIDEND POLICY AND INVESTMENT DECISIONS ON FIRM VALUE HIDIV-20 INDEX - Yuliana, Intan Putri; Sartika, Farahiyah (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2025)
This study investigates how dividend policy and investment decision influence the firm value of HIDIV 20 index companies, using earning quality as a moderating factor variable. By applying a sample purposive method, a selection of 20 companies on the IDX from 2020 to 2023 is analyzed. The analysis found that dividend policy has an impact on firm value, while investment decisions have no impact. impact. This study also found that earnings quality moderates the relationship between dividend policy and investment decisions on firm value. Results of this study should be considered by investors who base their investment decisions on a company’s dividend policy, investment decisions, and earnings quality.